Beef Cow-Calf Enterprise - Fogleman, Sarah L.; Jones, Rodney D. (My University, 2001)
This publication provides a budget based on projected input and output prices. This budget is based on a typical spring calving cow herd with natural breeding.
MF266_2001_10
Keywords: MF266; Livestock; Economics; MF